98.7k views
3 votes
What is equivalent to the expression 3x(x-2)+7x-1

User Shadoweb
by
4.6k points

2 Answers

3 votes
Here you go…………….. ……
What is equivalent to the expression 3x(x-2)+7x-1-example-1
User Gonzalo S
by
5.0k points
5 votes

Hey there!

3x(x - 2) + 7x - 1

DISTRIBUTE 3x WITHIN the PARENTHESES

= 3x(x) + 3x(-2) + 7x - 1

= 3x^2 - 6x + 7x - 1

COMBINE the LIKE TERMS

= (3x^2) - 6x + 7x - 1

= 3x^2 + 1x - 1

= 3x^2 + x - 1

Therefore, your answer is: “3x^2 + x - 1” OR you could say “3x^2 + 1x - 1” because they are both equivalent to each other

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Kina
by
5.2k points